PENGARUH KUALITAS LAYANAN, CITRA MEREK, KEPERCAYAAN DAN BAURAN PEMASARAN WEB TERHADAP LOYALITAS - Rahayu Rahayu (KELOLA: Jurnal Ilmiah Manajemen, 2021)
The DKI Government is trying to increase the number of visitors to the Thousand Islands tourist by increasing various facilities and infrastructure through online and of line services.To get to know about the performance of Wisata kepulauan seribu pulau Untung Jawa the hypotheses that need to be answer are (1) the influence of service quality toward loyalty (2) the influence of brand image toward loyalty (3) the influence of trust toward loyalty and (4) the influence of web marketing mix toward loyalty. The study design used is a combination of verificative statistic and descriptive statistic, while research method used is survey approach, data are collected questionnaire with a total  of  150 respondents Untung Jawa tourists. Sampling technique is done by purpose sampling . The method of analysis uses descriptive statistic average, and SEM method by using software Lisrel . The result show on the descriptive analysis toward the variable used is positive and some are negative. The SEM result analysis toward the hypothesis test based on imphirical data of 4 hypotheses proven are service quality is proven to be significantly influence loyalty , brand image is proven to be significantly influence loyalty and trust is proven to be significantly influence loyalty , and web  marketing mix is proven to be significantly influence loyalty .